2019
DOI: 10.21203/rs.2.15576/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explaining the successes and failures of tuberculosis treatment programs; a tale of two regions in rural Eastern Uganda

Abstract: Background Well performing tuberculosis (TB) programs are characterized by treatment success rate (TSR) of at least 90%. In rural eastern Uganda, and elsewhere in sub Saharan Africa, TSR varies considerably across district TB programs and the reasons for the differences are unclear. This study explored factors that explain the low and high TSR across four districts in rural eastern Uganda.Methods We interviewed District TB and Leprosy Supervisors (DTLS), Laboratory focal persons (LFPs) and TB focal persons (TB… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The increased workload was mostly attributed to a lack of human resources in the facility as staff recommended that increased human resources could offset the strained workload. Shea et al's study findings were consistent with our findings and similarly recommended for the recruitment of more staff plus provision of additional support to improve readiness levels [28]. Another identified challenge was that staff may not have devoted time for the program within their overwhelmed schedule which might impede implementation.…”
Section: Task Demandssupporting
confidence: 88%
See 1 more Smart Citation
“…The increased workload was mostly attributed to a lack of human resources in the facility as staff recommended that increased human resources could offset the strained workload. Shea et al's study findings were consistent with our findings and similarly recommended for the recruitment of more staff plus provision of additional support to improve readiness levels [28]. Another identified challenge was that staff may not have devoted time for the program within their overwhelmed schedule which might impede implementation.…”
Section: Task Demandssupporting
confidence: 88%
“…nurses, charge nurses, administrators and medical directors) [21, 28]. Therefore for future work, it is worthy to note that some questions in readiness tools may have more of a clinical meaning for participants, for example in our study that were majorly nurses as compared to other studies that had mostly leaders who may have more of an administrative meaning [28].…”
Section: Discussionmentioning
confidence: 92%
“…This improvement may be attributable to improvements in healthcare system over time: better staffing and improved healthcare provider competence and confidence to manage persons with BC-PTB through mentorships and coaching, and better counseling among others. Elsewhere [38], healthcare providers indicated that tuberculosis clinics have been established across most health facilities to provide more time to understand and solve the challenges of persons with tuberculosis. This approach has led to better management of persons with tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in eastern Uganda reports that inadequate financing of the TB control program and deficiencies in the implementation of the CB-DOTS strategy is associated with suboptimal treatment success [16]. The study further showed that the disappearance of symptoms of TB especially after treatment initiation results in DTT [16].…”
Section: Discussionmentioning
confidence: 78%
“…A previous study in eastern Uganda reports that inadequate financing of the TB control program and deficiencies in the implementation of the CB-DOTS strategy is associated with suboptimal treatment success [16]. The study further showed that the disappearance of symptoms of TB especially after treatment initiation results in DTT [16]. Physical and economic barriers have been reported in a previous study as one of the reasons for not completing required sputum smear monitoring visits [17], emphasizing that people with TB face several barriers along the pathway to continuing with treatment.…”
Section: Discussionmentioning
confidence: 99%